2004
DOI: 10.1021/ja048919w
|View full text |Cite
|
Sign up to set email alerts
|

Oligoacenes:  Theoretical Prediction of Open-Shell Singlet Diradical Ground States

Abstract: A series of oligoacenes from benzene to decacene were studied computationally with DFT and CASSCF methods. In contrast to the common view that acenes are closed-shell systems or may have a triplet ground state, these results offer the first theoretical predictions for the singlet ground state and diradical character for oligoacenes. The nature of the ground states of these molecules arises from the disjoint nature of the NBMOs that are singly occupied in the diradical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

55
636
1
8

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 704 publications
(700 citation statements)
references
References 15 publications
55
636
1
8
Order By: Relevance
“…It was recently shown that the lowest energy state of higher polyacenes can correspond to diradical singlet state instead of the closed-shell singlet state [59][60][61]. Similar results are also observed for some studied quinones.…”
Section: Resultssupporting
confidence: 77%
“…It was recently shown that the lowest energy state of higher polyacenes can correspond to diradical singlet state instead of the closed-shell singlet state [59][60][61]. Similar results are also observed for some studied quinones.…”
Section: Resultssupporting
confidence: 77%
“…Houk has observed a similar effect for polyacenes, some of which are computed by DFT to have open-shell singlet ground states as a result of the disjoint nature of the triplet SOMOs (that study also employed the broken-symmetry method for the singlet states). 47 The disjoint nature of the triplet SOMOs for this ion 13 contrasts with the xanthenyl ions (1−8) and coumarinyl ions (17−19), which share SOMO wave function amplitude on some of the same atoms (Figure 2). Thus, for these latter species the triplet configuration would be expected to have a non-negligible exchange energy and is computed to be lower in energy than the open-shell singlet configuration.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 93%
“…Indeed, this hexagonal nano-flake has attracted great interest with respect to its interesting properties like electronic absorption spectra, 119 and it has been successfully applied for modeling graphene in previous theoretical work. [120][121][122][123][124] Several theoretical studies have focussed on acenes [125][126][127] and oligoacenes [128][129][130][131][132] using DFT and ab-initio methods. However, because of the polyradical character of oligoacenes, 125,126 the spin ground state of these molecules have to be checked.…”
Section: Graphene Modelmentioning
confidence: 99%
“…[120][121][122][123][124] Several theoretical studies have focussed on acenes [125][126][127] and oligoacenes [128][129][130][131][132] using DFT and ab-initio methods. However, because of the polyradical character of oligoacenes, 125,126 the spin ground state of these molecules have to be checked. Singlet-triplet (S-T) excitation energies give valu- 137 The first S-S and S-T excitation energies were calculated to 1.94 and 1.77 eV, respectively.…”
Section: Graphene Modelmentioning
confidence: 99%